Osseous Metaplasia and Bone Marrow Elements in a Case of Renal Cell Carcinoma - Seyma Ozkanli; Asif Yildirim; Ebru Zemheri; Sarp Korcan Keskin; Erem Kaan Basok (Case Reports in Urology)
Renal cell carcinoma with osseous metaplasia and bone marrow elements is a relatively rare event in these tumors. We discuss pathological differential diagnosis for this tumor with a review of the literature on this unusual case.